Ovsey Shkaratan (1931–2019) - Editorial Board (Journal of Economic Sociology, 2019)
Professor Shkaratan, who passed away on July 31, 2019, was a professor emeritus of the Higher School of Economics, head of the Laboratory of Comparative Analysis of Post-Socialist Societies (National Research University Higher School of Economics), as well as founder and editor-in-chief of the journal Universe of Russia.